Implementing Early Sexual Education as a Preventive Measure against Sexual Harassment in Children - Ubaidillah, Khasan; Giyoto; Purnomo, SF Luthfie Arguby (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Educational Institutions must address the rising incidence of sexual harassment against children by systematic prevention measures, such as the early introduction of sexual education. Conducting this research is crucial in order to ascertain the extent to which early childhood education institutions are implementing sexual education at a young age in accordance with children's developmental stages and in a consistent effort to prevent sexual harassment against children. The research employed a qualitative descriptive technique, conducted between July and September 2023. The subject of this study is the classroom teacher, while the informants are the curriculum teacher, the health-responsible teacher, and the school principal of BA Aisiyah Cawas. The methods employed for data collection encompassed observation, interviews, and documentation. To verify the validity of the research data, the researchers used the techniques of method triangulation and source triangulation. Meanwhile, data analysis methods include condensation, presentation, and conclusion drawing. The findings of this study indicate that Early Childhood Education Institutions can effectively reduce sexual harassment by adopting comprehensive sexual education programs that specifically target early-stage sexual education. The implemented measures encompass acquainting children with anatomical structures and their respective functions, instructing children on independent genital hygiene (toilet training), educating children on permissible and impermissible contact with body parts, segregating sleeping arrangements by gender, exemplifying healthy interpersonal relationships, fostering adherence to hygienic practices, and imparting knowledge on safeguarding oneself against sexual harassment. Keywords: Prevention strategies, sexual harassment, sexual education & children.